2013
DOI: 10.1007/s00210-013-0949-x
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of montelukast, a cysteinyl leukotriene receptor antagonist, against methotrexate-induced kidney damage in rats

Abstract: Methotrexate (MTX) is a cytotoxic chemotherapeutic agent used for treatment of several cancers. Nephrotoxicity, an adverse side effect of high-dose MTX, is attributed to abnormal production of reactive oxygen species (ROS), inflammatory mediators, and neutrophil infiltration. Montelukast (MON) is a cysteinyl leukotriene receptor antagonist. Recently, it has gained a considerable interest as a ROS scavenger and inflammatory modulator. In this study, we investigated the effect of MON against MTX-induced nephroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 51 publications
5
39
0
6
Order By: Relevance
“…Several hypotheses have been suggested for the mechanisms underlying MTX toxicity, including the involvement of oxidative stress, inflammation, and apoptosis . MTX toxicity increases NOx in the tissues, leading to generation of peroxynitrite radicals that damage the cell . The oxidative stress which occurred by MTX administration in agreement with previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…Several hypotheses have been suggested for the mechanisms underlying MTX toxicity, including the involvement of oxidative stress, inflammation, and apoptosis . MTX toxicity increases NOx in the tissues, leading to generation of peroxynitrite radicals that damage the cell . The oxidative stress which occurred by MTX administration in agreement with previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…It was reported that 20 mg/kg dose of Mtx, used in this study, highly exceeds interval dose and can be accepted as high dose Mtx in human (Oktem et al, 2006;Cetinkaya et al, 2007;Abdel-Raheem and Khedr, 2014). Mtx treatment at high doses may cause renal failure (Abelson et al, 1983).…”
Section: Discussionmentioning
confidence: 77%
“…TNF‐α, IL‐1β, IL‐6, and NF‐κB levels were assessed as markers of inflammation (Abdel‐Raheem & Khedr, ; Çakir et al, ; Elks et al, ). Their levels were significantly elevated ( p < .05) in the MTX‐treated animals compared to the control group.…”
Section: Resultsmentioning
confidence: 99%